Radicalising Social Work: Involving Everyone; Including All Our Knowledges - Beresford, Peter (Participatory Social Work: Research, Practice, Education, 2019)
This discussion focuses on participation as an approach to radicalising social work, drawing on the experience of the author and many others in the UK and beyond. It explores the modern history of participation in policy and ideology, highlighting the empirical evidence that many people seem to feel they have little say over their lives and institutions affecting them and regard this as problematic. It highlights inequalities in participation and explores different ideological approaches to participation; their strengths and weaknesses, the emergence of service user movements; the gains from involving service users in research and the methodological and practical issues of excluding and including people’s “experiential” or first hand knowledge as both practitioners and service users, the overlaps between the two groups, the importance of involving practitioners too and key issues emerging for participation.